Information and Communication Technologies for Ageing Well and e-Health : Third International Conference, ICT4AWE 2017, Porto, Portugal, April 28-29, 2017, Revised Selected Papers /: Third International Conference, ICT4AWE 2017, Porto, Portugal, April 28-29, 2017, Revised Selected Papers. (2018) - Unknown
No abstract available